2007
DOI: 10.1038/sj.hdy.6801040
|View full text |Cite
|
Sign up to set email alerts
|

Environment-dependent trade-offs between ectoparasite resistance and larval competitive ability in the Drosophila–Macrocheles system

Abstract: Costs of resistance are expected to contribute to the maintenance of genetic variation for resistance in natural host populations. In the present study, we experimentally test for genetic trade-offs between parasite resistance and larval competitive ability expressed under varying levels of crowding and temperature. Artificial selection for increased behavioral resistance was applied against an ectoparasitic mite (Macrocheles subbadius) in replicate lines of the fruit fly Drosophila nigrospiracula. We then mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Similarly, the trade-off between resistance to bacterial infection and fecundity in D. melanogaster is erased when the flies are provided with a protein-enriched diet (McKean et al 2008), and was not observed in a similar experiment performed in a different laboratory . Drosophila melanogaster larvae selected for resistance to Asobara parasitization and D. nigrospiracula selected for resistance to mites are outcompeted by susceptible larvae, but only under high density conditions (Kraaijeveld & Godfray 1997;Luong & Polak 2007b). In very rich environments, genetic correlations between physiologically linked traits may even become positive, as genetic variation for acquisition of resources from the environment becomes more prominent than variation for allocation of resources to competing traits (e.g.…”
Section: Pleiotropy and Competing Physiologiesmentioning
confidence: 99%
“…Similarly, the trade-off between resistance to bacterial infection and fecundity in D. melanogaster is erased when the flies are provided with a protein-enriched diet (McKean et al 2008), and was not observed in a similar experiment performed in a different laboratory . Drosophila melanogaster larvae selected for resistance to Asobara parasitization and D. nigrospiracula selected for resistance to mites are outcompeted by susceptible larvae, but only under high density conditions (Kraaijeveld & Godfray 1997;Luong & Polak 2007b). In very rich environments, genetic correlations between physiologically linked traits may even become positive, as genetic variation for acquisition of resources from the environment becomes more prominent than variation for allocation of resources to competing traits (e.g.…”
Section: Pleiotropy and Competing Physiologiesmentioning
confidence: 99%
“…Mites in the genus Macrocheles disperse between breeding sites by attaching themselves to Drosophila nigrospiracula adults that reduces the latter's fitness. Artificial selection for improved behavioral defenses leads to a reduction in fecundity, especially in stressed files (Luong and Polak 2007a,b) Drosophila larvae are attacked by specialist parasitoid wasps (Hymenoptera) that lay their eggs in early‐instar larvae. The parasitoid does not progress beyond the first instar until its host has pupated and during this period of suspended development the egg and larva have to avoid encapsulation, the cellular immune response mounted by invertebrates to natural enemies too big to phagocytose (Meister and Lagueux 2003).…”
mentioning
confidence: 99%
“…The maintenance of heritable variation for resistance may result from the costs of resistance (Luong and Polak, 2007), leading to genetic trade-offs between resistance and other fitness-related traits (Sheldon and Verhulst, 1996). A gene (antagonistic pleiotropy), or a set of linked genes (linkage disequilibrium), having a favourable effect on one trait and an unfavourable effect on another trait, forms the genetic basis for such trade-offs.…”
Section: Introductionmentioning
confidence: 99%